Mucosa-associated lymphoid tissue lymphoma translocation protein 1 exaggerates multiple organ injury, inflammation, and immune cell imbalance by activating the NF-κB pathway in sepsis - Wang, Yane; Liu, Zhimin; Zhang, Mengli; Yu, Bo; Ai, Fen (Frontiers in Microbiology, 2023)
Objective Mucosa-associated lymphoid tissue lymphoma translocation protein 1 (MALT1) modulates the inflammatory immune response and organ dysfunction, which are closely implicated in sepsis pathogenesis and progression. This study aimed to explore the role of MALT1 in sepsis-induced organ injury, immune cell dysregulation, and inflammatory storms. Methods Septic mice were constructed by intraperitoneal injection of lipopolysaccharide, followed by overexpression or knockdown of MALT1 by tail vein injection of the corresponding lentivirus. Mouse naïve CD4+ T cells and bone marrow-derived macrophages were treated with MALT1 overexpression/knockdown lentivirus plus lipopolysaccharide. Results In the lungs, livers, and kidneys of septic mice, MALT1 overexpression exaggerated their injuries, as shown by hematoxylin and eosin staining (all p < 0.05), elevated cell apoptosis, as reflected by the TUNEL assay and cleaved caspase-3 expression (p < 0.05 in the lungs and kidneys), and promoted macrophage infiltration, as illustrated by CD68 immunofluorescence (p < 0.05 in the lungs and kidneys). Meanwhile, in the blood, MALT1 overexpression reduced T-helper (Th)1/Th2 cells, increased Th17/regulatory T-cell ratios (both p < 0.05), promoted systematic inflammation, as revealed by tumor necrosis factor-α, interleukin-6, interleukin-1β, and C-reactive protein (all p < 0.05), elevated oxidative stress, as shown by nitric oxide (p < 0.05), superoxide dismutase, and malondialdehyde (p < 0.05), and enhanced liver and kidney dysfunction, as revealed by an automatic animal biochemistry analyzer (all p < 0.05 except for aspartate aminotransferase). However, MALT1 knockdown exerted the opposite effect as MALT1 overexpression. Ex vivo experiments revealed that MALT1 overexpression promoted the polarization of M1 macrophages and naïve CD4+ T cells toward Th2 and Th17 cells (all p < 0.05), while MALT1 knockdown attenuated these effects (all p < 0.05). Mechanistically, MALT1 positively regulated the nuclear factor-κB (NF-κB) pathway both in vivo and ex vivo (p < 0.05). Conclusion Mucosa-associated lymphoid tissue lymphoma translocation protein 1 amplifies multiple organ injury, inflammation, oxidative stress, and imbalance of macrophages and CD4+ T cells by activating the NF-κB pathway in sepsis.